Multi-scale hybrid particle reinforced aluminum-based composite material and SLM (selective laser melting) preparation method thereof

Through multi-scale hybrid particle enhancement and SLM process optimization, the problems of limited performance improvement space and SLM forming defects in the existing technology are solved, and high-strength, high-toughness, and high-hardness aluminum-based composite materials are achieved, and the preparation of high-strength, high-strength, and high-hardness is achieved. Its application potential in lightweight and integrated manufacturing.

CN119282107APending Publication Date: 2025-01-10XIAN UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411414857.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In the preparation of high-performance aluminum-based composite materials, it is difficult to improve strength, toughness and hardness at the same time. In the SLM forming process, there are defects such as sintering spheroidization and thermal cracks, which are difficult to ensure the material density, and it is difficult to take into account multiple properties of a single reinforcement. need.

Method used

Multi-scale mixed particles reinforced aluminum-based composite materials are used to optimize particle content and powder preparation process, and combined with the optimization of SLM process parameters, high-strength, high-toughness and high hardness aluminum-based composite materials are prepared. The specific methods include using AlSi10Mg atomized powder, micron-scale Al2O3, nano-scale Al2O3 and sub-micron-scale SiC powder, using ultrasonic dispersion and low-energy ball mill to prepare composite powder, and shaping through a selected laser melting forming system, controlling laser power, scanning speed and Scan the spacing.

Benefits of technology

It has achieved the improvement of high strength, toughness and hardness of aluminum-based composite materials, reduced costs, improved the density and mechanical properties of materials, and expanded its application potential in aerospace, automobile and other industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119282107A_ABST
    Figure CN119282107A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-scale hybrid particle reinforced aluminum-based composite material, which is prepared from the following raw material powder in percentage by mass: 70 to 98.5 percent of AlSi10Mg atomized powder, 0.5 to 20 percent of micron-sized Al2O3 powder, 0.5 to 20 percent of nano-sized Al2O3 powder and 0.5 to 20 percent of submicron-sized SiC powder, and the sum of the mass percent of the components is 100 percent. The material is an aluminum-based composite material with high strength, high toughness and high hardness. The invention further provides an SLM preparation method of the multi-scale hybrid particle reinforced aluminum-based composite material, through particle content optimization, powder preparation process innovation and SLM process parameter optimization, the high-strength, high-toughness and high-hardness aluminum-based composite material is obtained, and additive manufacturing of the aluminum-based composite material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing technology and metal-based composite materials, and specifically relates to a multi-scale hybrid particle reinforced aluminum-based composite material, and also relates to a SLM preparation method of the multi-scale hybrid particle reinforced aluminum-based composite material. Background Art

[0002] Metal matrix composites are widely used in many industrial fields due to their excellent comprehensive mechanical properties. Traditional methods for preparing metal matrix composites mainly include powder metallurgy, pressure casting, extrusion, etc., which have the following problems: (1) long process flow and high cost; (2) low material utilization and poor near-net forming capability; (3) it is difficult to prepare components with complex shapes and complex internal structures; (4) process parameters are easily restricted by equipment, molds, etc., and quality stability and repeatability are poor.

[0003] Selective laser melting (SLM) is an emerging metal 3D printing technology that uses a high-energy laser beam to selectively melt metal powder layer by layer to directly manufacture three-dimensional complex components. Compared with traditional processes, SLM has the following advantages: (1) No mold is required, and complex and special-shaped components can be directly manufactured; (2) High material utilization rate and less waste; (3) Short production cycle and low cost of small batch customized production; (4) Laser melting and rapid solidification form fine and uniform grains with excellent mechanical properties. Therefore, SLM technology has shown great application potential in high-end manufacturing fields such as aerospace and biomedicine.

[0004] However, SLM forming of aluminum alloys faces the following technical challenges: (1) Aluminum alloys have high thermal conductivity and low laser energy utilization; (2) Aluminum alloys are prone to sintering spheroidization, thermal cracking and other defects during the SLM process; (3) SLM formed parts are prone to residual holes, unfused parts and other defects, making it difficult to ensure density; (4) It is difficult for a single reinforcement to simultaneously improve strength, toughness and hardness. Therefore, it is urgent to develop a high-performance aluminum-based composite material system that can be formed by SLM.

[0005] At present, the common method of strengthening and modifying aluminum alloys is to add hard particles, such as ceramics, intermetallic compounds, etc. There are many kinds of reinforcement particles that have been reported, especially expensive carbon materials such as diamond, carbon nanotubes (CNT), and graphene are also often used as reinforcements for aluminum alloys. However, most traditional reinforcement methods use a single type and single scale of particles, or two types but without multi-scale gradation characteristics to improve the mechanical properties of composite materials. It is difficult to take into account multiple performance requirements such as strength, toughness, and hardness.

[0006] Previous research has focused on micron-scale particle enhancement, while ignoring the composite enhancement effect of particles of different sizes, such as nanometers and submicrometers. Only a few studies have involved nanoparticle enhancement, but there are problems such as uneven dispersion and serious agglomeration, which makes it difficult to fully exert the nano-enhancement effect, restricting its promotion and application in the industrial field. This is mainly due to the large specific surface area, high surface energy, and easy agglomeration of nanoparticles. How to achieve uniform dispersion of nanoparticles during the preparation process is a major challenge.

[0007] In addition, SLM forming process parameters (such as laser power, scanning speed, scanning spacing, etc.) have a decisive influence on the quality of the formed parts. However, traditional parameter optimization is mostly aimed at a single material system, and rarely considers the forming characteristics of composite materials. The addition of different reinforcing particles will inevitably affect the melting, solidification, and densification behavior of the matrix. Targeted research is needed to optimize the process window in order to obtain high-performance SLM additive manufacturing composite components.

[0008] In summary, the performance improvement space of a single reinforcement system is limited, and it is urgent to develop a new multi-component, multi-scale composite reinforcement system. At the same time, it is necessary to overcome the difficulties of uniform dispersion of nanoparticles and optimization of SLM forming process, and promote the 3D printing preparation and engineering application of high-performance aluminum-based composite materials. Summary of the invention

[0009] The first object of the present invention is to provide a multi-scale hybrid particle reinforced aluminum-based composite material, which is an aluminum-based composite material with high strength, high toughness and high hardness.

[0010] The second object of the present invention is to provide an SLM preparation method for multi-scale mixed particle reinforced aluminum-based composite materials, and to obtain high-strength, high-toughness, and high-hardness aluminum-based composite materials by optimizing particle content, innovating powder preparation technology, and optimizing SLM process parameters, and to realize its additive manufacturing.

[0011] The first technical solution adopted by the present invention is that the multi-scale mixed particle reinforced aluminum matrix composite material is composed of the following raw material powders according to mass percentage: 70-98.5% AlSi10Mg atomized powder, micron-sized Al 2 O 3 Powder 0.5~20%, nano-grade Al 2 O 3 The powder is 0.5-20%, and the submicron SiC powder is 0.5-20%, and the sum of the mass percentages of the above components is 100%.

[0012] The present invention is also characterized in that:

[0013] Micron Al 2 O 3 The average particle size of the powder is 1μm to 10μm, and the nano Al 2O 3 The average particle size of the powder is 10nm to 100nm, and the average particle size of the submicron SiC powder is 0.1μm to 1μm.

[0014] The second technical solution adopted by the present invention is a method for preparing a multi-scale hybrid particle reinforced aluminum-based composite material, comprising the following steps:

[0015] Step 1: Weigh the following by mass percentage: AlSi10Mg atomized powder 70-98.5%, micron-sized Al 2 O 3 Powder 0.5~20%, nano-grade Al 2 O 3 Powder 0.5-20%, submicron grade SiC powder 0.5-20%, the sum of the mass percentages of the above components is 100%;

[0016] Step 2: Preparation of composite powder for SLM;

[0017] Step 3: Use a selective laser melting forming system (SLM forming system) to prepare multi-scale mixed particle reinforced aluminum matrix composites.

[0018] The present invention is also characterized in that:

[0019] Step 2 is as follows:

[0020] Step 2.1: weigh the micron-sized Al 2 O 3 Powder, nano-scale Al 2 O 3 The powder and submicron SiC powder are sequentially added into anhydrous ethanol medium at a solid-liquid ratio of 1:(1-5), and ultrasonically dispersed and mechanically stirred to obtain a ceramic suspension;

[0021] Step 2.2: Mix AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add agate balls or zirconia balls with diameters of 10mm, 15mm, and 20mm, respectively, with a ball-to-material ratio of 1 to 3:1, and use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 5min to 30min, stop for 5min to 30min, reverse for 5min to 30min, and so on until the total time reaches 5h to 8h; after ball milling, dry the powder at 30℃ to 80℃, sieve, and obtain a composite powder for SLM. In step 2.1, first disperse nano-Al in anhydrous ethanol. 2 O 3 10min~30min, then add submicron SiC and continue to disperse for 10min~30min, and finally add micron Al 2 O 3And disperse for 10min to 30min; ultrasonic power 100W to 500W, total dispersion time 10min to 60min. In step 2.2, agate balls or zirconia balls with diameters of 10mm, 15mm and 20mm are used in a mass ratio of 2:3:5, and the ball milling time is 2h to 8h; the rotation speed is 100rpm to 400rpm. In step 3: the three key parameters of laser power P, scanning speed v, and scanning spacing h in the selective laser melting forming system are 180W to 280W, 600mm / s to 800mm / s, and 50μm to 90μm respectively; chessboard partition scanning is adopted, the partition size is 1.5mm to 3.5mm×1.5mm to 3.5mm, and the scanning direction of each layer is staggered by 30o to 90o. The substrate is preheated to 100℃ to 300℃, and the forming chamber is filled with high-purity argon gas for protection, and the oxygen content is controlled below 0.1%.

[0022] The beneficial effects of the present invention are:

[0023] (1) The method of the present invention uses micron Al 2 O 3 、Nano Al 2 O 3 and submicron SiC, two Al 2 O 3 The AlSi10Mg-based composite material is prepared by using the reinforced particles of the components, and the multi-component and multi-scale synergistic reinforcement mechanism is used to improve the material strength (≥400MPa) and hardness (≥180HV 0.3 ) while ensuring excellent toughness (≥5%), expanding the performance control space of aluminum-based composite materials and providing new ideas for their lightweight applications in aerospace, automotive, electronics and other industries. Compared with commonly used CNT, graphene and other reinforcements, Al 2 O 3 And SiC ceramic particles can significantly reduce the cost of composite materials.

[0024] (2) The method of the present invention adopts a "two-step method" of ultrasonic dispersion combined with low-energy ball milling to prepare composite powders, which solves the problem of nano-Al 2 O 3 The problem of uniform dispersion of submicron SiC particles was solved. First, the three ceramic particles were dispersed in an ethanol medium by gradient ultrasonic dispersion, and the cavitation effect of ethanol molecules and the "small leads to large" mechanism were used to inhibit the agglomeration of nanoparticles; then they were low-energy ball milled with AlSi10Mg powder, using intermittent forward and reverse modes to avoid excessive cold welding. Compared with the traditional ball milling process, the particle uniformity, loose density, fluidity and other indicators of the prepared composite powder were significantly improved. This method can reduce SLM forming defects and reduce the cost of powder preparation, and has significant process advantages and application value.

[0025] (3) The method of the present invention optimizes the SLM process parameters to obtain near-net-shape parts with high density (≥97.5%) and fine grains (≤5μm). The laser power, scanning speed, and scanning spacing are controlled in the range of 180-280W, 600-800mm / s, and 50-90μm, respectively, to ensure sufficient melting while avoiding material burnout and pore defects. The use of partitioned and staggered scanning, preheating the substrate to 100-300℃, and Ar atmosphere protection can reduce residual stress and prevent cracking. Compared with unoptimized parameters, the density is increased by more than 2%, and the strength, toughness, and hardness are increased by 25%, 30%, and 15%, respectively. Compared with conventional manufacturing methods (such as casting), the comprehensive mechanical properties of SLM-formed composite materials are improved by more than 30%.

[0026] (4) The composite material of the present invention and a single micron-sized Al 2 O 3 Compared with particle reinforcement, multi-scale hybrid Al 2 O 3 The mechanical properties of the synergistic reinforcement system of Al / SiC are comprehensively improved, with strength, elongation at break and hardness increased by 20%, 50% and 10% respectively, and the cost is reduced by more than 10%. Compared with carbon-based reinforcements such as CNT and graphene, the present invention adopts Al 2 O 3 , SiC ceramic particles, can reduce the cost of composite materials by more than 50%, and have obvious advantages in dispersibility, interface bonding strength, machinability, etc. Therefore, the present invention achieves the performance improvement of AlSi10Mg-based composite materials while reducing costs, greatly expanding its application space.

[0027] In summary, the present invention systematically improves the preparation level and application value of AlSi10Mg-based composite materials in terms of materials, processes, performance, costs, etc., and shows great advantages in lightweight and integrated manufacturing. It is of great significance to promote the 3D printing application of metal-based composite materials in aerospace, automotive, electronics and other industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 For SLM forming (Al 2 O 3 +SiC) particle hybrid reinforced aluminum matrix composites;

[0029] Figure 2 For SLM forming (Al 2 O 3 +SiC) particle hybrid reinforced aluminum matrix composites. DETAILED DESCRIPTION

[0030] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0031] The present invention provides a multi-scale mixed particle reinforced aluminum-based composite material, which is composed of the following raw material powders according to mass percentage: 70-98.5% AlSi10Mg atomized powder, micron-sized Al 2 O 3 Powder 0.5~20%, nano-grade Al 2 O 3 The multi-scale hybrid particle reinforced aluminum matrix composite material is based on AlSi10Mg atomized powder and mixed with three sizes of reinforced ceramic particles: micron Al 2 O 3 , nano-Al 2 O 3 , submicron SiC, forming a multi-scale hybrid reinforced powder.

[0032] Among them, micron Al 2 O 3 The average particle size of the powder is 1μm to 10μm, and the nano Al 2 O 3 The average particle size of the powder is 10nm to 100nm, and the average particle size of the submicron SiC powder is 0.1μm to 1μm.

[0033] Al 2 O 3 The particles have excellent mechanical properties, chemical stability and wear resistance; SiC particles have the characteristics of high hardness, high strength, high modulus, etc. The strengthening mechanisms of particles of different sizes in the matrix are different, and they cooperate with each other and complement each other: (1) Micron Al 2 O 3 The particles are dispersed in the matrix, hindering dislocation movement and providing dislocation strengthening. Large-sized second phase particles can effectively hinder crack propagation. (2) Nano-Al 2 O 3 The particles have a large specific surface area, a high distribution density in the matrix, and a strong interface with the matrix, which can not only play a role in dispersion strengthening, but also refine the grains and provide grain boundary strengthening. 2 O 3 The particles can be filled between the micron reinforcing particles, playing a role of "support" and "lubrication", and improving the uniformity of ball milling dispersion of the composite powder. (3) Submicron SiC particles play a role of carbide dispersion strengthening in the matrix, improving the hardness of the composite material. At the same time, the residual compressive stress generated by the mismatch of thermal expansion coefficients between SiC and the matrix further strengthens the material.

[0034] In summary, micron Al 2 O 3 Provide dislocation strengthening, nano Al 2 O3 Provide dispersion strengthening and grain boundary strengthening, submicron SiC particles play a role in carbide strengthening and residual stress strengthening, multiple strengthening mechanisms work together, and the three constitute a multi-scale synergistic reinforcement system, making the tensile strength of the composite material not less than 400MPa, the elongation at break not less than 5%, and the Vickers hardness not less than 180HV 0.3 Compared with single strengthening, the strengthening mechanism of this system is more diverse and can give full play to the advantages of various mechanisms. 2 O 3 The addition of particles is conducive to the uniform dispersion of submicron SiC particles in the matrix, embodying the idea of ​​"leading the big with the small".

[0035] Nano Al 2 O 3 The particles can be filled in micron Al 2 O 3 Between particles, improve the dispersion uniformity of composite powder during ball milling, submicron SiC particles in nano-Al 2 O 3 The particles are evenly dispersed due to the "lubrication" effect.

[0036] The present invention also provides a method for preparing a multi-scale hybrid particle reinforced aluminum-based composite material, comprising the following steps:

[0037] Step 1: Weigh the following by mass percentage: AlSi10Mg atomized powder 70-98.5%, micron-sized Al 2 O 3 Powder 0.5~20%, nano-grade Al 2 O 3 Powder 0.5-20%, submicron grade SiC powder 0.5-20%, the sum of the mass percentages of the above components is 100%;

[0038] Step 2: Prepare composite powder for SLM using a "two-step method";

[0039] Step 2 is as follows:

[0040] Step 2.1: weigh the micron-sized Al 2 O 3 Powder, nano-scale Al 2 O 3 The powder and submicron SiC powder are sequentially added into anhydrous ethanol medium at a solid-liquid ratio of 1:1 to 5, and ultrasonically dispersed and mechanically stirred to obtain a ceramic suspension;

[0041] In step 2.1, nano-Al is first dispersed in anhydrous ethanol. 2 O 310min~30min, then add submicron SiC and continue to disperse for 10min~30min, and finally add micron Al 2 O 3 And disperse for 10min~30min; ultrasonic power is 100W~500W, and the total dispersion time is 10min~60min.

[0042] Step 2.2: Mix the AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add agate balls or zirconia balls with diameters of 10 mm, 15 mm, and 20 mm, respectively, and the ball-to-material ratio is 1 to 3:1. Use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 5 min to 30 min, stop for 5 min to 30 min, reverse for 5 min to 30 min, and repeat this cycle until the total time reaches 5 h to 8 h; after ball milling, dry the powder at 30 ° C to 80 ° C, sieve, and obtain a composite powder for SLM.

[0043] In step 2.2, agate balls or zirconia balls of three specifications with diameters of 10 mm, 15 mm and 20 mm are prepared in a mass ratio of 2:3:5, the ball milling time is 2 h to 8 h, and the rotation speed is 100 rpm to 400 rpm.

[0044] The combination and ratio of agate ball diameters in step 2.2 can achieve adequate mixing of powders under low energy conditions.

[0045] The "intermittent forward and reverse" ball milling mode adopted in step 2.2 can further effectively inhibit the agglomeration of powders during the ball milling process.

[0046] The characteristics of this step are: (1) low-energy ball milling avoids plastic deformation and excessive cold welding caused by high energy density; (2) "intermittent" and "forward and reverse" modes use inertial force to avoid agglomeration caused by long-term unidirectional movement; (3) agate or zirconia has moderate hardness, which is conducive to breaking up agglomerates. After the ball milling is completed, the powder is dried and sieved to obtain a composite powder for SLM.

[0047] The above-mentioned "two-step method" process can obtain a composite powder that is evenly dispersed and free of agglomeration, and is simple to operate, low in cost, and suitable for industrial applications. Compared with the traditional ball milling process, this method can disperse nanoparticles more effectively.

[0048] In terms of powder ratio, through systematic research, it is found that the optimal mass fraction range of AlSi10Mg matrix is ​​70-98.5%. When it is lower than 70%, the matrix content is too low and the composite effect is poor; when it is higher than 98.5%, the strengthening effect is not obvious. 2 O 3 、Nano Al 2 O 3The optimal addition amounts of 3D SiC and submicron SiC are 0.5-20%, 0.5-20%, and 0.5-20%, respectively. Too high or too low amounts are not conducive to the strengthening effect.

[0049] Step 3: Use a selective laser melting forming system (SLM forming system) to prepare multi-scale mixed particle reinforced aluminum matrix composites.

[0050] In step 3: the three key parameters of the laser power P, scanning speed v, and scanning spacing h in the selective laser melting forming system are 180W~280W, 600mm / s~800mm / s, and 50μm~90μm respectively; chessboard partition scanning is adopted, the partition size is 1.5mm~3.5mm×1.5mm~3.5mm, and the scanning direction of each layer is staggered 30o~90o. The substrate is preheated to 100℃~300℃, and the forming chamber is filled with high-purity argon for protection, and the oxygen content is controlled below 0.1%.

[0051] The process parameter range selected in step 3 can obtain a composite material with a high density (≥97.5%) and a fine grain size (average ≤5 μm) with a moderate laser energy density.

[0052] The checkerboard partitioning and staggered scanning strategy adopted in step 3 can reduce thermal stress and deformation and suppress anisotropy.

[0053] The preheating treatment of the substrate and the atmosphere protection of the forming chamber in step 3 can effectively reduce the temperature difference between the substrate and the formed part, reduce thermal stress, and prevent oxidation.

[0054] In terms of SLM forming process optimization, the present invention focuses on three key parameters: laser power (P), scanning speed (v), and scanning spacing (h). Studies have found that when P, v, and h are controlled in the range of 180-280W, 600-800mm / s, and 50-90μm, respectively, while ensuring densification (≥97.5%), a composite material with a small grain size (≤5μm) and excellent mechanical properties can be obtained. If the laser power is too high, the material is prone to evaporation and burning; if the power is too low, the melting is insufficient. If the scanning speed is too fast, the heat input is insufficient; if it is too slow, the matrix elements evaporate seriously. If the scanning spacing is too large, unfused defects are likely to occur between passes; if it is too small, the matrix and reinforcing particles are prone to excessive melting.

[0055] In addition, the present invention optimizes the scanning strategy and substrate preheating process. The "chessboard" partition scanning is adopted, and each area is scanned in turn. The scanning direction of each layer is staggered by 67°, which can reduce residual thermal stress and deformation. Preheating the substrate to 200°C can reduce the temperature difference between the substrate and the molten pool and reduce thermal stress. The forming process is carried out in an inert atmosphere (such as high-purity Ar, etc.). 2 Controlling the content below 0.1% can prevent oxidation of aluminum alloy and SiC particles.

[0056] In summary, the present invention has carried out a systematic and in-depth study from multiple aspects such as material system construction, powder preparation process optimization, and SLM forming parameter selection, thereby obtaining a multi-scale hybrid Al with high density and high mechanical properties. 2 O 3 / SiC particle reinforced AlSi10Mg based composites.

[0057] Example 1

[0058] The preparation method of the multi-scale hybrid particle reinforced aluminum matrix composite material comprises the following steps:

[0059] Step 1: Weigh the following by mass percentage: AlSi10Mg atomized powder (average size 30 μm) 98.5%, micron-grade Al 2 O 3 Powder (1μm) 0.5%, nano-grade Al 2 O 3 Powder (100nm) 0.5%, submicron SiC powder (1μm) 0.5%, the sum of the mass percentages of the above components is 100%;

[0060] Step 2: Preparation of composite powder for SLM;

[0061] Step 2 is as follows:

[0062] Step 2.1: weigh the micron-sized Al 2 O 3 Powder, nano-scale Al 2 O 3 The powder and submicron SiC powder were sequentially added into anhydrous ethanol medium with a solid-liquid ratio of 1:5, and ultrasonically dispersed and mechanically stirred to obtain a ceramic suspension;

[0063] In step 2.1, nano-Al is first dispersed in anhydrous ethanol. 2 O 3 10 min, then add submicron SiC and continue to disperse for 10 min, and finally add micron Al 2 O 3 And disperse for 10 minutes; ultrasonic power 100W, total dispersion time 10 minutes.

[0064] Step 2.2: Mix the AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add agate balls with diameters of 10 mm, 15 mm, and 20 mm, respectively, and the ball-to-material ratio is 1:1. Use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 15 minutes, stop for 15 minutes, reverse for 15 minutes, and repeat this cycle until the total time reaches 5 hours; after ball milling, dry the powder at 80°C and pass through a 150-mesh sieve to obtain a composite powder for SLM.

[0065] In step 2.2, agate balls of three sizes with diameters of 10 mm, 15 mm and 20 mm were milled in a mass ratio of 2:3:5, with a ball milling time of 2 h and a rotation speed of 400 rpm.

[0066] Step 3: Use a selective laser melting forming system (SLM forming system) to prepare multi-scale mixed particle reinforced aluminum matrix composites.

[0067] In step 3: the process parameters used in the selective laser melting forming system are: laser power 180W, scanning speed 600mm / s, scanning spacing 50μm. Partition scanning, area 2.5mm×2.5mm, staggered 67°. The substrate is preheated to 200℃, and the forming chamber is filled with high-purity argon gas for protection, and the oxygen content is controlled below 0.1%.

[0068] Test results: tensile strength 413.55MPa, elongation at break 5.43%, hardness 198HV 0.3 , density 97.6%, average grain size 4.8μm. Figure 1 It can be seen that the tensile strength of the material is as high as 413.55MPa, indicating that it has a high strength level, which is due to the addition of the reinforcement phase and the strengthening effect of the matrix. At the same time, the elongation of the material at fracture reaches 5.43%, which is a considerable value for high-strength aluminum-based composite materials, indicating that the material has both excellent plasticity and toughness. Figure 2 For SLM forming (Al 2 O 3 +SiC) particles hybrid reinforced aluminum matrix composite material, it can be seen that the matrix is ​​aluminum alloy, the average grain size is 4.8μm, in which multi-level micron, submicron and nanometer ceramic particles are dispersed inside the aluminum grains and grain boundaries. These particles are Al 2 O 3 and SiC, which play a role in enhancing the performance of the matrix. As can be seen in the figure, the reinforcing particles are uniform in size and relatively evenly distributed, tightly bonded to the matrix, and have no obvious pores or defects. There is no cracking or delamination between the particles and the matrix, indicating that the interface is well bonded. Overall, the composite material has the microstructural characteristics of a typical particle-reinforced composite material. The evenly distributed ceramic particles can effectively strengthen the matrix and improve the mechanical properties of the material, especially the strength and hardness. This high-quality microstructure is the microscopic basis for the excellent mechanical properties of the material.

[0069] Example 2

[0070] The preparation method of the multi-scale hybrid particle reinforced aluminum matrix composite material comprises the following steps:

[0071] Step 1: Weigh the following by mass percentage: 80% AlSi10Mg atomized powder (average size 30 μm), 80% micron-sized Al 2 O 3 Powder (10μm) 10%, nano-grade Al 2 O 3 Powder (1nm) 5%, submicron SiC powder (100nm) 5%, the sum of the mass percentages of the above components is 100%;

[0072] Step 2: Preparation of composite powder for SLM;

[0073] Step 2 is as follows:

[0074] Step 2.1: weigh the micron-sized Al 2 O 3 Powder, nano-scale Al 2 O 3 The powder and submicron SiC powder were sequentially added into anhydrous ethanol medium with a solid-liquid ratio of 1:1, and ultrasonically dispersed and mechanically stirred to obtain a ceramic suspension;

[0075] In step 2.1, nano-Al is first dispersed in anhydrous ethanol. 2 O 3 20min, then add submicron SiC and continue to disperse for 20min, and finally add micron Al 2 O 3 And disperse for 20 minutes; ultrasonic power is 300W, and the total dispersion time is 30 minutes.

[0076] Step 2.2: Mix the AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add zirconia balls with diameters of 10 mm, 15 mm, and 20 mm, respectively, with a ball-to-material ratio of 2:1, and use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 5 minutes, stop for 5 minutes, reverse for 5 minutes, and repeat this cycle until the total time reaches 8 hours; after ball milling, dry the powder at 30°C and pass through a 150-mesh sieve to obtain a composite powder for SLM.

[0077] In step 2.2, three sizes of zirconia balls with diameters of 10 mm, 15 mm and 20 mm were mixed in a mass ratio of 1:1:1, the ball milling time was 8 h, and the rotation speed was 100 rpm.

[0078] Step 3: Use a selective laser melting forming system (SLM forming system) to prepare multi-scale mixed particle reinforced aluminum matrix composites.

[0079] In step 3: the process parameters used in the selective laser melting forming system are: laser power 280W, scanning speed 700mm / s, scanning spacing 70μm. Partition scanning, area 1.5mm×1.5mm, staggered 30°. The substrate is preheated to 100℃, and the forming chamber is filled with high-purity argon for protection, and the oxygen content is controlled below 0.1%.

[0080] Test results: tensile strength 480MPa, elongation at break 6.5%, hardness 225HV 0.3 , density 98.8%, average grain size 3.5μm.

[0081] Example 3

[0082] The preparation method of the multi-scale hybrid particle reinforced aluminum matrix composite material comprises the following steps:

[0083] Step 1: Weigh the following by mass percentage: 70% AlSi10Mg atomized powder (average size 30 μm), 70% micron-sized Al 2 O 3 Powder (5μm) 20%, nano-grade Al 2 O 3 Powder (10nm) 5%, submicron SiC powder (500nm) 5%, the sum of the mass percentages of the above components is 100%;

[0084] Step 2: Preparation of composite powder for SLM;

[0085] Step 2 is as follows:

[0086] Step 2.1: weigh the micron-sized Al 2 O 3 Powder, nano-scale Al 2 O 3 The powder and submicron SiC powder were sequentially added into anhydrous ethanol medium with a solid-liquid ratio of 1:3, and ultrasonically dispersed and mechanically stirred to obtain a ceramic suspension;

[0087] In step 2.1, nano-Al is first dispersed in anhydrous ethanol. 2 O 3 30min, then add submicron SiC and continue to disperse for 30min, and finally add micron Al 2 O 3 And disperse for 30 minutes; ultrasonic power 500W, total dispersion time 60 minutes.

[0088] Step 2.2: Mix the AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add agate balls with diameters of 10 mm, 15 mm, and 20 mm, respectively, and the ball-to-material ratio is 3:1. Use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 30 minutes, stop for 30 minutes, reverse for 30 minutes, and repeat this cycle until the total time reaches 6 hours; after ball milling, dry the powder at 60°C and pass through a 150-mesh sieve to obtain a composite powder for SLM.

[0089] In step 2.2, agate balls of three sizes with diameters of 10 mm, 15 mm and 20 mm were milled in a mass ratio of 3:5:6, the ball milling time was 5.5 h, and the rotation speed was 250 rpm.

[0090] Step 3: Use a selective laser melting forming system (SLM forming system) to prepare multi-scale mixed particle reinforced aluminum matrix composites.

[0091] In step 3: the process parameters used in the selective laser melting forming system are: laser power 180W, scanning speed 800mm / s, scanning spacing 90μm. Partition scanning, area 3.5mm×3.5mm, staggered 90°. The substrate is preheated to 300℃, and the forming chamber is filled with high-purity argon for protection, and the oxygen content is controlled below 0.1%.

[0092] Test results: tensile strength 530MPa, elongation at break 5.6%, hardness 260HV 0.3 , density 97.9%, average grain size 2.8μm.

[0093] Comparative Example 1 (single micron-level enhancement, traditional ball milling process)

[0094] (1) AlSi10Mg powder (90wt%) and micronized Al 2 O 3 (10wt%, 1~10μm) mixed.

[0095] (2) Add the mixed powder into a stainless steel ball mill with a ball-to-material ratio of 1:1 and mill for 5.5 hours at a rotation speed of 300 rpm.

[0096] (3) The ball-milled powder is passed through a 150-mesh sieve to obtain a composite powder for SLM.

[0097] (4) The specimen was formed using the same SLM process parameters as in Example 2.

[0098] (5) Test results: tensile strength 395 MPa, elongation at break 4.2%, hardness 210 HV0.3, density 96.5%, average grain size 6.5 μm.

[0099] Comparative Example 2 (without nano-Al2 O 3 , the other conditions are the same as in Example 2)

[0100] (1) AlSi10Mg powder (85wt%) and micronized Al 2 O 3 (10wt%) and submicron SiC (5wt%) mixed.

[0101] (2) The ultrasonic dispersion, ball milling and SLM forming conditions are the same as those in Example 2.

[0102] (3) Test results: tensile strength 210MPa, elongation at break 0.6%, hardness 105HV 0.3 , density 92.2%, average grain size 15.8μm.

[0103] Comparative Example 3 (different SLM process parameters)

[0104] (1) The powder composition and preparation method are the same as in Example 2.

[0105] (2) SLM process parameters: laser power 150 W, scanning speed 1000 mm / s, scanning interval 100 μm, and other conditions are the same as in Example 2.

[0106] (3) Test results: tensile strength 160 MPa, elongation at break 1.8%, hardness 140 HV0.3, density 91.1%, average grain size 18.2 μm.

[0107] It can be seen from Examples 1 to 3 that as Al 2 O 3 As the total content of SiC increases from 1.5wt% to 30wt%, the strength of the composite material increases from 410MPa to 530MPa, and the hardness increases from 198HV0.3 to 260HV 0.3 , thanks to Al 2 O 3 , the synergistic effect of dispersion strengthening, dislocation strengthening, and grain boundary strengthening brought about by the increase of SiC content. At the same time, the density and average grain size are maintained above 97.5% and below 5μm, respectively, and the elongation at break is above 5%, indicating that the synergistic reinforcement of multi-scale particles can ensure good toughness while improving strength and hardness. In contrast, the strength and hardness of Comparative Example 1 are lower than those of Example 2, and the elongation at break and grain size are also poor. This is because the use of a single micron-sized Al 2 O 3When the particles are reinforced, the strengthening mechanism is single and the particle agglomeration phenomenon is obvious. This shows that it is difficult for the traditional single reinforcement system to take into account multiple mechanical properties such as strength, toughness, and hardness. The comprehensive mechanical properties of comparative example 2 are inferior to those of example 2, especially the elongation at break is significantly reduced and the grain size becomes larger. This shows that when nano-Al2O3 particles are missing, the dispersion strengthening and grain boundary strengthening effects of the composite material are weakened, and it is difficult to obtain ideal mechanical properties. It can be seen that nano-Al 2 O 3 The particles play a key role in improving the toughness of the composite material and refining the grains. The density and mechanical properties of Comparative Example 3 are far inferior to those of Example 2. The main reasons are that the laser power is low, the scanning speed is too fast, the scanning spacing is too large, and the heat input is seriously insufficient, resulting in insufficient material melting, coarse grains, and more pore defects. This shows that the optimization of SLM process parameters is crucial to the densification of composite materials and the regulation of organizational properties.

Claims

1. A multi-scale hybrid particle reinforced aluminum matrix composite material, characterized in that: The invention is composed of the following raw material powders according to mass percentage: 70-98.5% of AlSi10Mg atomized powder, 0.5-20% of micron-grade Al2O3 powder, 0.5-20% of nano-grade Al2O3 powder and 0.5-20% of submicron-grade SiC powder, and the sum of the mass percentages of the above components is 100%.

2. The multi-scale hybrid particle reinforced aluminum matrix composite material according to claim 1, characterized in that: The average particle size of the micron Al2O3 powder is 1 μm to 10 μm, the average particle size of the nano Al2O3 powder is 10 nm to 100 nm, and the average particle size of the submicron SiC powder is 0.1 μm to 1 μm.

3. A method for preparing a multi-scale hybrid particle reinforced aluminum matrix composite material, characterized in that: The following steps are involved: Step 1: Weigh the following components by mass percentage: 70-98.5% AlSi10Mg atomized powder, 0.5-20% micron-grade Al2O3 powder, 0.5-20% nano-grade Al2O3 powder, and 0.5-20% submicron-grade SiC powder, the sum of the mass percentages of the above components being 100%; Step 2: Preparation of composite powder for SLM; Step 3: Use a selective laser melting forming system to prepare multi-scale mixed particle reinforced aluminum matrix composites.

4. The method for preparing the multi-scale hybrid particle reinforced aluminum-based composite material according to claim 3, characterized in that: Step 2 is as follows: Step 2.1: Add the weighed micron-sized Al2O3 powder, nano-sized Al2O3 powder and submicron-sized SiC powder into anhydrous ethanol medium in sequence, with a solid-liquid ratio of 1:1-5, and perform ultrasonic dispersion and mechanical stirring to obtain a ceramic suspension; Step 2.2: Mix the AlSi10Mg powder with the ceramic suspension obtained in step 2.1, add agate balls or zirconia balls with diameters of 10 mm, 15 mm, and 20 mm, respectively, and the ball-to-material ratio is 1 to 3:

1. Use a planetary ball mill for low-energy ball milling; adopt an "intermittent forward and reverse" ball milling method, specifically: forward rotation for 5 min to 30 min, stop for 5 min to 30 min, reverse for 5 min to 30 min, and repeat this cycle until the total time reaches 5 h to 8 h; after ball milling, dry the powder at 30 ° C to 80 ° C, sieve, and obtain a composite powder for SLM.

5. The method for preparing the multi-scale hybrid particle reinforced aluminum-based composite material according to claim 4, characterized in that: In step 2.1, nano-Al2O3 is first dispersed in anhydrous ethanol for 10 min to 30 min, then submicron SiC is added and dispersed for another 10 min to 30 min, and finally micron Al2O3 is added and dispersed for 10 min to 30 min; the ultrasonic power is 100 W to 500 W, and the total dispersion time is 10 min to 60 min.

6. The method for preparing the multi-scale hybrid particle reinforced aluminum-based composite material according to claim 4, characterized in that: In step 2.2, agate balls or zirconia balls of three specifications with diameters of 10 mm, 15 mm and 20 mm are prepared in a mass ratio of 2:3:5, the ball milling time is 2 h to 8 h, and the rotation speed is 100 rpm to 400 rpm.

7. The method for preparing a multi-scale hybrid particle reinforced aluminum-based composite material according to claim 4, characterized in that: In step 3: the three key parameters of the laser power P, scanning speed v, and scanning spacing h in the selective laser melting forming system are 180W~280W, 600mm / s~800mm / s, and 50μm~90μm respectively; chessboard partition scanning is adopted, the partition size is 1.5mm~3.5mm×1.5mm~3.5mm, the scanning direction of each layer is staggered by 30°~90°, the substrate is preheated to 100℃~300℃, and the forming chamber is filled with high-purity argon for protection, and the oxygen content is controlled below 0.1%.

Citation Information

Cited By

  • Method for enhancing mechanical property of laser metal deposition TiAl alloy through micro-nano TiC particles

    CN121178872A

  • Method for enhancing mechanical properties of laser metal deposition TiAl alloy by micro-nano TiC particles

    CN121178872B